2016
DOI: 10.1177/1754073915615430
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Species Comparative Approach to Positive Emotion Disturbance

Abstract: Recent discoveries stress the importance of studying positive emotion disturbances (PED) yet there remains little empirical work or integrative conceptual framework in this domain. We suggest that an ideally suited opportunity to advance the study of PED is to consider a cross-species evolutionary framework. We apply this framework-drawing from principles of stabilizing selection-to recent empirical findings in humans and nonhumans suggesting how positive emotion and associated play behaviors may lead to detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…For example, in a systematic review study, Lyubomirsky et al ( 2005 ) documented that there are various tangible benefits of well-being such as better general health, effective coping strategies, fulfilling social relationships, and success. More recently, similar findings have been reported concerning the link between well-being and health outcomes (Gruber and Bekoff 2017 ; Huang and Humphreys 2012 ; Kansky and Diener 2017 ), and self-productivity, success, subjective vitality, meaning, self-esteem, and marital satisfaction (Akdağ and Cihangir-çankaya 2015 ; Braaten et al 2019 ).…”
supporting
confidence: 69%
“…For example, in a systematic review study, Lyubomirsky et al ( 2005 ) documented that there are various tangible benefits of well-being such as better general health, effective coping strategies, fulfilling social relationships, and success. More recently, similar findings have been reported concerning the link between well-being and health outcomes (Gruber and Bekoff 2017 ; Huang and Humphreys 2012 ; Kansky and Diener 2017 ), and self-productivity, success, subjective vitality, meaning, self-esteem, and marital satisfaction (Akdağ and Cihangir-çankaya 2015 ; Braaten et al 2019 ).…”
supporting
confidence: 69%
“…Rather, when experiencing a set of diverse emotions, people are presented with varied emotional stimuli, so that the responses are kept active (Leventhal et al 2007). Last but not the least, experiencing a diversity of emotions may reduce the vulnerability to detrimental events by preventing an overabundance of one specific emotion from dominating people's emotional life (Benson et al 2017;Gruber and Bekoff 2017).…”
Section: Tourists' Emotion and Emodiversitymentioning
confidence: 99%
“…Last but not the least, experiencing a diversity of emotions may reduce the vulnerability to detrimental events by preventing an overabundance of one specific emotion from dominating people’s emotional life (Benson et al. 2017; Gruber and Bekoff 2017).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…That is, the ability to characterize affective information with precision (i.e., in terms of qualitatively distinct events) may reduce the potential for individuals to make misattributions about their own affective reactions (Schwarz, 1990; Schwarz & Clore, 1983). Finally, experiencing a diversity of emotional states might reduce vulnerability to affective psychopathology by preventing an overabundance or prolonging of any one emotion from dominating an individuals’ emotional life (Benson, et al, in press; Gruber & Bekoff, 2017). Supporting this logic, Quoidbach and colleagues (2014) found that greater emodiversity was associated with better mental and physical health.…”
Section: Emodiversity and Healthmentioning
confidence: 99%